Carbapenemase Gene Profiles in Carbapenem-Resistant Enterobacteriaceae—United States, January 2018–August 2019. (October 2020) - Huang, Jennifer; Pettinger, Amanda; Bantle, Katie; Bhatnagar, Amelia; Gilbert, Sarah; Malik, Sarah
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) cause significant morbidity and mortality each year in the United States. Treatment options for these infections are often limited, in part due to carbapenemases, which are mobile β-lactam-hydrolyzing enzymes that confer multidrug resistance in CRE. As part of the CDC's Containment Strategy for Emerging Resistance, public health laboratories (PHLs) in the CDC Antibiotic Resistance Laboratory Network (AR Lab Network) have worked to characterize clinical isolates of CRE for rapid identification of carbapenemase genes. These data are then used by public health and healthcare partners to promote patient safety by decreasing the spread of resistance. We summarize carbapenemase gene profiles in CRE, by genus and geography, using data collected through the AR Lab Network from January 2018 through August 2019. Methods: CRE isolates were submitted to 55 PHLs, including those of all 50 states, 4 large cities, and Puerto Rico, in accordance with each jurisdiction's reporting laws. PHLs performed phenotypic and molecular testing on isolates to detect targeted, emerging carbapenemase genes and reported results to submitters. Carbapenemase-positive (CP) isolates were defined as PCR positive for ≥1 carbapenemase gene tested: bla KPC, bla NDM, bla VIM, bla IMP, bla OXA-48–LIKE. PHLs submitted results to CDC monthly. Genera other than Enterobacter, Klebsiella, and Escherichia coli are categorized as other genera in this analysis. Data were compiled and analyzed using SAS v 9.4 software. Results: From January 2018 to August 2019, the AR Lab Network tested 25, 705 CRE isolates; 8, 864 of 25, 705 CRE (34%) were CP. Klebsiella spp represented the largest proportion of CP-CRE at 68% (n = 6, 063), followed by E. coli (12%, n = 1, 052), Enterobacter spp (11%, n = 981), and other genera (9%, n = 768). Figure 1a shows the composition of CP-CRE carbapenemase genes by genus. The most common carbapenemase and genus profiles were bla KPC in Klebsiella (74%; 5, 562 of 7, 561 bla KPC-positive) blaNDM in E. coli (43%; 372 of 868 bla NDM-positive) bla VIM in Enterobacter spp (35%; 25 of 72 bla VIM-positive), and bla IMP among other genera (90%; 92 of 102 bla IMP-positive). Common CP-CRE genes and genera also varied by geography (Fig. 1b). Conclusions: The AR Lab Network has greatly enhanced our nation's ability to detect and characterize CP-CRE. Our data provide a snapshot of the organisms and regions where mobile carbapenemase genes are most often detected in CRE. Geographic variation in CP gene profiles provides actionable data to inform local priorities for detection and infection control and provide clinicians with situational awareness of the genes and organisms that are circulating in their region. Funding: None Disclosures: In this presentation, the authors discuss the drug combination aztreonam-avibactam and acknowledge that this drug combination is not currently FDA-approved.